Designing a Frequency Measurement Instrument Kit Based on the PIC16F628A Microcontroller - Ganjar Febriyani Pratiwi; Roby Fenki Mahardika Prawiro; Erfiana Wahyuningsih; Tri Nur Arifin (International Journal of Science and Environment (IJSE), 2026)
The rapid development of electronic systems has increased the need for accurate frequency measurement because many electrical and digital devices depend on stable operating frequencies for proper performance. In routine laboratory and field work, digital multimeters are frequently used for frequency checks due to their practicality and availability, yet their readings may be affected by signal conditions and instrument processing limits. This study aims to assemble and evaluate a low-cost digital frequency counter based on the PIC16F628A microcontroller for measuring crystal oscillators and external frequency signals, while benchmarking its readings against a digital multimeter. An experimental quantitative approach was applied that included hardware assembly, schematic reconstruction through PCB trace inspection, block-level functional analysis, and measurement testing using five crystal oscillators and externally generated reference signals derived from a 32.768 kHz source with frequency division. Data were recorded across test points from 1 Hz to 32.768 kHz and summarized through direct comparison between nominal frequencies and instrument readings. The frequency counter produced readings that matched the nominal test frequencies across all external test points within the display resolution limits. Crystal testing also yielded values close to nominal specifications (e.g., 8.0002 MHz for 8 MHz and 11.998 MHz for 12 MHz). The digital multimeter showed small frequency-dependent offsets at higher test points (e.g., 32.770 kHz at 32.768 kHz). These results indicate that the dedicated counter delivers stable measurements across the evaluated range. This work offers a practical reference for electronics education and routine verification by combining schematic reconstruction, reproducible block-level documentation, and empirical validation of a kit-based instrument, providing added value beyond prior studies that emphasize either theory or new system design.